Mengidentifikasi Strategi Promosi pada Jasa Penjualan Saldo Digital menggunakan Pendekatan Clustering - Hamka Surya Nugraha; Hilman Mutaqin; Adittia Fathah; Christina Juliane (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
The rapid development of information technology has impacted various fields, one of which is cellular telephony. The increasing number of people who have cell phones impacts the need for digital products, especially digital balances, which are increasing. This study aims to identify digital balance sales so that they become input, especially the ZAR counter-promotion strategy. This study uses the clustering method and the K-Means Algorithm to obtain several clusters of transaction types based on the nominal sales price. The silhouette is used to find the number of clusters. The dataset used in this study is the sale of digital ZAR counterbalances from November 2021 to October 2022. This research resulted in a total of 2 clusters. First cluster with low price nominal sales was 49,213 data, while second with high nominal price sales was 3,076. The study results show that the k-means algorithm can be used to cluster sales of ZAR counter digital balances, and ZAR counter digital balances are quite good. Still, there is data in clusters with high nominal prices. ZAR counter owners can create promotional strategies by providing discounts below 142,000 so that customers who buy at a high nominal price move to a lower nominal price.